FISTULA ARTERIOVENOSUS FASIALIS PADA KEHAMILAN - Risky Ilona Saputra; Kumara Tini (NEURONA, 2018)
FACIAL ARTERIOVENOSUS FISTULA IN PREGNANCYABSTRACTArteriovenosus fistula (AVF) of superficial temporal artery is rarely found. We report a case of 34 years old women, with facial AVF during her third pregnancy. The patient was admitted to the hospital with complain of pulsating headache, tinnitus, and pulsating mass on the left preauricular  region. Arteriovenosus fistula diagnosis was confirmed by Digital Substraction Angiography (DSA), showing the left superficial temporal artery as the feeding artery. The headache and tinnitus was diminished immidiately after embolization procedure followed by ligation surgery.Keywords: Arteriovenosus fistula, pregnancy, superficial temporal arteryABSTRAKFistula arteriovenosus (FAV) pada arteri temporalis superfisialis (ATS) jarang ditemukan. Dilaporkan kasus seorang perempuan berusia 34 tahun yang mengalami FAV fasial dalam kehamilan anak ketiganya. Pasien mengeluhkan nyeri kepala berdenyut, tinnitus, dan massa berdenyut pada area preaurikularis kiri. Pemerikasan digital substraksi angiografi (DSA) mengkonfirmasi adanya FAV, dengan feeding artery berasal dari ATS kiri. Setelah tindakan embolisasi dan operasi penutupan fistula, keluhan nyeri kepala dan tinnitus menghilang.Kata kunci: Arteri temporalis superfisialis, fistula arteriovenosus, kehamilan